2019
DOI: 10.1177/1071100719882679
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of Deltoid Ligament Integrity in Ankle Fractures

Abstract: Background: Regardless of fibular status, the presence of a superficial deltoid ligament disruption or a combination of deep and superficial deltoid ligament disruption is central to the decision-making process in treating ankle fractures. The aims of the present study were to test whether ultrasonography can assess deltoid ligament integrity and to determine its validity and reliability by comparing it with gravity stress radiography. Methods: A consecutive series of 81 eligible patients with a nondisplaced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
2
12
0
4
Order By: Relevance
“…However, the methodological quality of that study is questionable since the study population was relatively small, the examiner was not blinded to the findings of the reference test and there was a non-consecutive patient selection process [21] . Nevertheless, results of Henari et al [21] were in line with Rosa et al [20] , who found a sensitivity of 1.00, a specificity of 0.90, a PPV of 0.97 and a NPV of 1.00 for ultrasonography. Results of present meta-analysis regarding ultrasonography combined with advantages like relative ease of use and no exposure to ionizing radiation, suggest that ultrasonography is an accurate and useful method to diagnose deltoid ligament rupture [20] .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, the methodological quality of that study is questionable since the study population was relatively small, the examiner was not blinded to the findings of the reference test and there was a non-consecutive patient selection process [21] . Nevertheless, results of Henari et al [21] were in line with Rosa et al [20] , who found a sensitivity of 1.00, a specificity of 0.90, a PPV of 0.97 and a NPV of 1.00 for ultrasonography. Results of present meta-analysis regarding ultrasonography combined with advantages like relative ease of use and no exposure to ionizing radiation, suggest that ultrasonography is an accurate and useful method to diagnose deltoid ligament rupture [20] .…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, results of Henari et al [21] were in line with Rosa et al [20] , who found a sensitivity of 1.00, a specificity of 0.90, a PPV of 0.97 and a NPV of 1.00 for ultrasonography. Results of present meta-analysis regarding ultrasonography combined with advantages like relative ease of use and no exposure to ionizing radiation, suggest that ultrasonography is an accurate and useful method to diagnose deltoid ligament rupture [20] .…”
Section: Discussionsupporting
confidence: 69%
“…The deltoid ligament plays a major role in limiting talar abduction, pronation, and external rotation, thus protecting the syndesmosis and the distal fibula. 2,5,8,19,41,43,49 Their combined injuries are therefore frequent. 34,51 Consideration of a DPTTL lesion associated with syndesmosis injury is important because it leads to external rotation of the tibiotalar joint, worsening the instability in favor of operative management.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of disruption, comparison between US and stress radiography revealed high sensitivity and specificity, proving that US is an accurate method for identifying the involved ligament components dynamically [203]. Although US may provide important information about the spring ligament complex and the ankle syndesmosis, available evidence for their US assessment is scarce [204].…”
Section: Medial Collateral Ankle Ligament (Deltoid) Complexmentioning
confidence: 99%